2022
DOI: 10.1016/j.amsu.2022.103347
|View full text |Cite
|
Sign up to set email alerts
|

A COVID-19 vaccination precipitating symptomatic calcific tendinitis: A case report

Abstract: Introduction Shoulder pathology may be symptomatic or asymptomatic depending on the patient. We report the first case of a COVID-19 vaccination administration precipitating symptomatic calcific tendinitis from pre-existing, asymptomatic calcific tendinitis. Case presentation A 50-year-old Thai male began experiencing left shoulder pain about 3 hours following a COVID-19 vaccination. He waited at home for the pain to improve, and when it did not improve in about 3 days h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
(25 reference statements)
0
4
0
Order By: Relevance
“…For subgroup purposes, that patient is counted in the cases from the literature [9] . In total, 28 patients were included from literature [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] .…”
Section: Resultsmentioning
confidence: 99%
“…For subgroup purposes, that patient is counted in the cases from the literature [9] . In total, 28 patients were included from literature [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] .…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, a case with intramuscular hematoma after vaccination resulting from iatrogenically erroneous injection site was also reported 31 . Another case with pre‐existing asymptomatic supraspinatus calcific tendinopathy suffered from shoulder pain and ROM limitation 3 hours after AZD‐1222 vaccination 36 . Although these etiologies of arthritis are also clinically important, they are neither listed in Table 3 nor included in analysis because they are beyond the scope of the review.…”
Section: Resultsmentioning
confidence: 99%
“…Other studies have suggested a subacromial subdeltoid bursitis as the primary pathology, 7-13 while there have also been case reports of calcific tendonitis. 14,15 Where there is isolated evidence of neuropathic changes in the axillary or radial nerve, there may be underlying iatrogenic damage due to inferior needle placement. 16,17 Diffuse weakness and neuropathic changes in non-dermatomal and myotomal patterns may indicate a brachial neuritis aetiology (Parsonage-Turner syndrome).…”
Section: Introductionmentioning
confidence: 99%